Ibnu Hibban: An Analysis of the Unique Methodology and Eligibility in Sahih Ibn Hibban - Manik, Zulfirman (Albayan Journal of Islam and Muslim Societies, 2024)
Abstract: This research is related to the methodology and conditions of hadith history used by Ibn Hibban in collecting the traditions in his Sahih book. To understand this theme, the research question is how the form of Ibn Hibban's methodology in collecting hadith and how the conditions determined by Ibn Hibban in determining the status of the hadith narrator contained in his Sahih book. This research uses qualitative type with content analysis approach. The data source comes from the Sahih book of Ibn Hibban with data collection through determining the object, creating categories and units of analysis. The findings of this study explain that the methodology of the compilation system of his sahih book, Ibn Hibban applies the qism-qism and nau'-nau' styles. Other findings found that in terms of the conditions used by Ibn Hibban in determining the status of the hadith narrator, namely judging the tsiqah of a person whose conditions are closed, that is, as long as there is no judgment of disgrace and judgment of 'fairness against him, every shaikh and narrator who narrates from him is tsiqah, and never brings a bad tradition. Finally, it can be emphasized that Ibn Hibban's methodology and the conditions for determining the narrator are unique because they are different from those used by ulama. Abstrak: Penelitian ini berkaitan dengan metodologi dan kondisi sejarah hadis yang digunakan oleh Ibnu Hibban dalam mengumpulkan tradisi dalam kitab Sahihnya. Untuk memahami tema tersebut, pertanyaan penelitian adalah bagaimana bentuk metodologi Ibnu Hibban dalam mengumpulkan hadis dan bagaimana kondisi yang ditentukan oleh Ibnu Hibban dalam menentukan status perawi hadis yang terkandung dalam kitab Sahihnya. Penelitian ini menggunakan tipe kualitatif dengan pendekatan analisis isi. Sumber data berasal dari kitab Sahih Ibnu Hibban dengan pengumpulan data melalui penentuan objek, pembuatan kategori dan unit analisis. Hasil penelitian ini menjelaskan bahwa metodologi sistem kompilasi kitab shahihnya, Ibnu Hibban menerapkan gaya qisme-qisme dan nau'-nau'. Temuan lain menemukan bahwa dari segi kondisi yang digunakan oleh Ibnu Hibban dalam menentukan status perawi hadis, yaitu menghakimi tsiqah seseorang yang kondisinya tertutup, yaitu selama tidak ada penghakiman aib dan penghakiman 'keadilan terhadapnya, setiap syekh dan perawi yang meriwayatkan darinya adalah tsiqah, dan tidak pernah membawa tradisi yang buruk. Akhirnya, dapat ditekankan bahwa metodologi Ibnu Hibban dan syarat-syarat penentuan perawi adalah unik karena berbeda dengan yang digunakan oleh ulama.